Living Well to Keep Your Pressure Down - Linda B. Bobroff (EDIS)
This document is FCS8690, one of a series of the Department of Family, Youth and Community Sciences, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Gainesville, FL 32611. Adapted from the NHLBI/NIH fact sheet “Facts About How to Prevent High Blood Pressure.” Publication: July 2002.